Holocene climate variations in the western Antarctic Peninsula: evidence for sea ice extent predominantly controlled by changes in insolation and ENSO variability - J. Etourneau; L. G. Collins; V. Willmott; J.-H. Kim; L. Barbara; A. Leventer; S. Schouten; J. S. Sinninghe Damsté; A. Bianchini; V. Klein; X. Crosta; G. Massé (Climate of the Past, 2013)
The West Antarctic ice sheet is particularly sensitive to global warming and its evolution and impact on global climate over the next few decades remains difficult to predict. In this context, investigating past sea ice conditions around Antarctica is of primary importance. Here, we document changes in sea ice presence, upper water column temperatures (0–200 m) and primary productivity over the last 9000 yr BP (before present) in the western Antarctic Peninsula (WAP) margin from a sedimentary core collected in the Palmer Deep Basin. Employing a multi-proxy approach, based on the combination of two biomarkers proxies (highly branched isoprenoid (HBI) alkenes for sea ice and TEX 86 L for temperature) and micropaleontological data (diatom assemblages), we derived new Holocene records of sea ice conditions and upper water column temperatures. The early Holocene (9000–7000 yr BP) was characterized by a cooling phase with a short sea ice season. During the mid-Holocene (~7000–3800 yr BP), local climate evolved towards slightly colder conditions and a prominent extension of the sea ice season occurred, promoting a favorable environment for intensive diatom growth. The late Holocene (the last ~2100 yr) was characterized by warmer temperatures and increased sea ice presence, accompanied by reduced local primary productivity, likely in response to a shorter growing season compared to the early or mid-Holocene. The gradual increase in annual sea ice duration over the last 7000 yr might have been influenced by decreasing mean annual and spring insolation, despite increasing summer insolation. We postulate that, in addition to precessional changes in insolation, seasonal variability, via changes in the strength of the circumpolar Westerlies and upwelling activity, was further amplified by the increasing frequency/amplitude of the El Niño–Southern Oscillation (ENSO). However, between 3800 and 2100 yr BP, the lack of correlation between ENSO and climate variability in the WAP suggests that other climatic factors might have ...